Role of the Gut Microbiota in the Development of Lipid and Carbohydrate Metabolism in the Liver Steatosis in Children - N.Yu. Zavgorodnya; E.V. Zygalo; O.Yu. Lukianenko; S.A. Babii (Zaslavsky O.Yu., 2016)
Background. Nonalcoholic fatty liver disease (NAFLD) is associated with insulin resistance, dyslipidemia and obesity. Recent evidence supports a role of the gut microbiota in the pathogenesis of NAFLD. Changes in the microbiota can lead to intestinal bile acids content modification and different signal pathways activation that can promote NAFLD progression. The aim of the study was to investigate carbohydrate and lipid spectrum of the blood in children with hepatic steatosis, depending on the degree of steatosis and the presence of bacterial overgrowth syndrome. Materials and methods. Study participants included 34 children aged 5 to 17 years. Determining the presence and degree of hepatic steatosis was conducted using FibroScan® 502 Touch with controlled attenuation parameter (CAP) measurement. According to the presence and degree of steatosis, patients were divided into 4 groups: group S0 was presented by 21 patients without hepatic steatosis (61.8 %), group S1 - 4 patients with degree 1 of steatosis (11.7 %), group S2 - 4 patients with degree 2 of steatosis (11.7 %), group S3 - 5 patients with degree 3 of steatosis (14.8 %). To diagnose the functional state of intestinal microbiota, we performed a hydrogen breath test with a load of lactose or glucose using gas analyzer Gastrolyzer. According to the hydrogen breath test results, patients were divided into 2 groups: the first group consisted of 7 patients with the presence of small intestine bacterial overgrowth (SIBO), the second group included 22 children without SIBO. Serum samples were tested for total cholesterol, triglycerides, high density lipoprotein cholesterol (HDL cholesterol). Serum insulin and glucose levels were defined and HOMA-IR was calculated. Results. Frequency of SIBO detection was higher and amounted to 33.3 % in patients with hepatic steatosis, 23.5 % - in patients without steatosis. SIBO has been mainly detected in the S3 group (75.0 %) (p <  0.05). In 50 % of patients with degree 3 of steatosis we detected SIBO in contrast to patients without SIBO, which had degree 1 and 2 of steatosis. Patients with SIBO had different types of dyslipidemia: dyslipidemia IIa type (34.0 %), type IIb (34.0 %), type IV (17.0 %) and an isolated lowering HDL cholesterol (17.0 %). Patients with SIBO also were characterized by higher level of HOMA-IR, which showed the development of insulin resistance. Conclusions. SIBO can be the possible cause of persistent dyslipidemia and insulin resistance in children with hepatic steatosis.